PENGGUNAAN METODE PROFILE MATCHING UNTUK PEMILIHAN EOSH CAPTAIN TERBAIK PADA PT.COCA-COLA INDONESIA - Mashyur, Riduan Syaiful; Frieyadie, Frieyadie (Jurnal Pilar Nusa Mandiri, 2019)
Environment, Occupational, Safety and Health (EOSH) Captain is an activity created by the Safety Officer at PT. Coca-Cola Indonesia. To determine the best EOSH Captain for the first time and is still influenced by the Subjective factor in assessing the prospective EOSH Captain, the safety officer is sometimes difficult to determine the best EOSH Captain, due to the lack of criteria so that the inaccuracy of assessment results in errors in determining the selection of EOSH Captain, constraints Another factor is the search for supporting data for the EOSH captain selection criteria is hampered, because the safety officer must focus on the job desk of his work, resulting in the length of the decision-making process. In this study, to overcome the above constraints, a method called the Profile Matching method is used. This Profile Matching method can process and compare the actual data value of a profile to be assessed with the expected profile value so that competency differences can be known. The purpose of this research is to accelerate the decision-making process. The assessment process will be more accurate, resulting in the determination of the selection of EOSH to be more precise and correct. The assessment process will be more accurate, resulting in the determination of the selection of EOSH to be more precise and correct. The results of calculations using the Profile Matching method above have obtained the greatest value and become the best EOSH captain is employee 17.